2003
DOI: 10.1097/00004836-200304000-00016
|View full text |Cite
|
Sign up to set email alerts
|

Early Activation of Peripheral Lymphocytes in Human Acute Pancreatitis

Abstract: Patients with severe pancreatitis show impaired early activation of peripheral CD19+ cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
18
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 13 publications
1
18
0
Order By: Relevance
“…Our study provides, probably for the first time, a broad and complex analysis of peripheral blood lymphocyte subsets with reference to different time points and different severity forms of acute pancreatitis. In agreement with the previous studies [7][8][9][10][11]16] , we also found a significant depletion of circulating lymphocytes which was much more profound in the severe form of pancreatitis. In the early period of 1-5 d of the disease, the magnitude of peripheral depletion was similar for T-(CD7+) and B-(CD19+) lymphocytes.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Our study provides, probably for the first time, a broad and complex analysis of peripheral blood lymphocyte subsets with reference to different time points and different severity forms of acute pancreatitis. In agreement with the previous studies [7][8][9][10][11]16] , we also found a significant depletion of circulating lymphocytes which was much more profound in the severe form of pancreatitis. In the early period of 1-5 d of the disease, the magnitude of peripheral depletion was similar for T-(CD7+) and B-(CD19+) lymphocytes.…”
Section: Discussionsupporting
confidence: 93%
“…Concerning the relations between these subsets of lymphocytes, the middle of the second week (d 10) was critical because of the strong predominance of T-over B-lymphocytes in S-AP. Depletion of the CD19+ lymphocyte subset in early acute pancreatitis has also been recently reported [16] .…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…Prior studies have shown an association between lower peripheral lymphocyte counts and the severity of cases of acute pancreatitis [31,32,33]. Such decline in lymphocyte count in acute pancreatitis was attributed to apoptosis and was also associated with lymphocyte dysfunction [34,35]. Additionally, prior studies have shown that a low lymphocyte count, together with a high neutrophil count, is associated with adverse outcomes in various other medical and surgical conditions [18,24,25].…”
Section: Discussionmentioning
confidence: 99%
“…Pezzilli et al 27 reported that the CD56-positive lymphocyte (NK-cell) count was not statistically different in acute pancreatitis. In this study, in patients with SAP, the incidence of abnormally low LAK cell activity, NK cell activity, and ADCC activity were 45.5%.…”
Section: Discussionmentioning
confidence: 99%